The effectiveness of modern chondroprotective therapy in patients with degenerative-dystrophic diseases of the spine associated with pain in the lower back - N. V. Yakovleva (Лечащий Врач)
An observational study of the effectiveness of the injectable Symptomatic Slow-Acting Drugs (SYSADOA) having chondroprotective activity was conducted in the amount of 10 injections, 1 injection of 2 ml every other day for 20 days. The study included 30 patients aged 40 to 65 years suffering from low back pain caused by degenerative-dystrophic diseases of the spine. Analysis of the results showed that therapy is effective in non-specific musculoskeletal low back pain at the prescribed dose: after 20 days of therapy of the low back pain in the studied group of patients decreased statistically significantly: from 70.1 ± 10.03 to 17.47 ± 8.94 on a 100-point visual-analog scale (p < 0.05); the average indicator of health status increased from 37.03 ± 14.49 to 87.6 ± 8.93, respectively (p < 0.05). Positive dynamics after 20 days of treatment was observed in all categories of the European Quality of Life Questionnaire (EQ-5D), health levels improved statistically significantly from the beginning to the end of the course of therapy (p < 0.05). According to the indicators of 100-point satisfaction with treatment, on average, patients were satisfied with therapy by 93.9 ± 5.97 points out of 100. Chondroprotective therapy made it possible to reduce the need for non-steroid anti-inflammatory drugs in patients, reduce their dose or do without non-steroid anti-inflammatory drugs during the course of treatment. Due to the convenient dosing regimen and rapid therapeutic effect, all patients demonstrated high compliance and completed the study according to plan. Thus, the proposed treatment regimen can be recommended for patients with pain syndrome in the lower back caused by degenerative-dystrophic diseases of the spine.